Surface modification of γ-TiAl alloys by acetylene plasma deposition - Suparut Narksitipan (2018)
Surfaces of two γ-TiAl alloys, Ti-47 at% Al-2at% Nb-2 at% Cr (MJ12) and Ti-47 at% Al-2 at% Nb-2 at% Mn + 0.8 at% TiB2(MJ47), have been modified by acetylene plasma deposition at bias voltages of -4, -5 and -6 kV for 3.6 × 103s (1 h) and 1.44 × 104s (4 h). Knoop hardness (HK) of the alloys is increased with the increase of bias voltage and prolonged time for the deposition. HK of MJ12 and MJ47 deposited at -6 kV for 1.44 × 104s is, respectively, 3.36 and 3.32 times as hard as the untreated alloys. SEM and AFM analyses show that the deposited alloys compose of a number of nano-dots which reflect their surface properties. The phases analyzed by XRD are in accord with the elements analyzed by EDX. © 2005 Elsevier B.V. All rights reserved.